POLA SOSIALISASI JAMAAH TABLIGH DALAM MENINGKATKAN SEMANGAT KEAGAMAAN DI JELUTUNG KELURAHAN DARUSSALAM KABUPATEN KARIMUN - Ma’ruf Riduan; T. Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research done to determine the pattern of socialization Tablighi Jamaat in Jelutung. This research focus is how to Tablighi Jamaat strategies undertaken in disseminating the values of Islam? and what obstacles faced in disseminating the values of Islam? while in this study using qualitative research methods, and retrieval of research subjects using purposive technique, which is based on research, specific reasons and according to the needs of research. The results of research carried out showed that the strategy carry out missionary in disseminating the values of Islam can be said is quod good, it is seen from the change in the individual and society are eager and excited to implement the fundamentals of religious teachings such as praying in congregation in the mosque, constantly gatherin, reading the al-qur’an and turn on the practices of other mosques. By using the pattern of socialization shaped jaulah, taklim wa taklum, science masa’il, venture prosper mosques, khidmat, khuruj fi Sabilillah and taklim masturah. And the run of barriers socialization Tablighi Jamaat in Jelutung not get too many constrains from the outside. Barries were a lot of self-arising, such as the the emergence of lazines, boredom, and problems of the time Tablighi Jamaat it self. While the barries from the outside is just a house visited by jamaah jaulah individuals were not at home. Not many obstacles encountered by the society because many are know Jelutung Tablighi Jamaat presence in their village.Key words : Tablighi Jamaat, Socialization pattern, Religious fervor